Aalto, Utzon, Fehn : three paradigms of phenomenological architecture - Tyrrell, Roger (Routledge, Taylor & Francis Group, 2018)
This book examines the work of three seminal Nordic architects - Alvar Aalto, Jorn Utzon and Sverre Fehn - from a phenomenological perspective, utilising the methodology of 'paradigm' (or 'in the manner of''). Roger Tyrrell explains how the approach of each architect is defined by the three sub-frames of the paradigm: that of the `origin' (arche), that of `revealing' (techne), and that of `the poetic conjunction', in order to gain a holistic understanding of the experiential or phenomenological predisposition of the three architects. Using this method the author describes the commonalties and distinctive qualities of the architecture and design methods of Aalto, Utzon and Fehn. The final chapter projects the intellectual heritage of the three protagonists into the contemporary world, examining the work of practices from the UK, Norway and the USA that each extend this particular way of making place.